The effect of a training programme on the empowerment status of women - Albertyn, Ruth M.(Ruth Meriel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Huishoudkunde) -- Universiteit van Stellenbosch, 1995.